Adenosine deaminase augments SARS-CoV-2 specific cellular and humoral responses in aged mouse models of immunization and challenge - Gary, Ebony N.; Tursi, Nicholas J.; Warner, Bryce M.; Cuismano, Gina; Connors, Jennifer; Parzych, Elizabeth M.; Griffin, Bryan D.; Bell, Matthew R.; Ali, Ali R.; Frase, Drew; Hojecki, Casey E.; Canziani, Gabriela A.; et al. (Frontiers in Immunology, 2023)
Despite numerous clinically available vaccines and therapeutics, aged patients remain at increased risk for COVID-19 morbidity. Furthermore, the aged patient population has suboptimal responses to SARS-CoV-2 vaccine antigens. Here, we characterized vaccine-induced responses to SARS-CoV-2 synthetic DNA vaccine antigens in aged mice. Aged mice had altered cellular responses, including decreased IFNγ secretion and increased TNFα and IL-4 secretion suggestive of increased TH2-type responses. Aged mice had significantly decreased total binding and neutralizing antibodies in their serum but significantly increased TH2-type spike-specific IgG1 antibody compared to their young counterparts and increased. Co-immunization with the plasmid-encoded molecular adjuvant adenosine deaminase-1 (pADA) enhanced IFNγ secretion while decreasing TNFα and IL-4 secretion and expanded the breadth and affinity SARS-CoV-2 spike-specific antibodies while supporting robust TH1-type humoral responses in aged mice. scRNAseq analysis of aged lymph nodes revealed that pADA co-immunization supported a strong TH1 gene profile and decreased FoxP3 gene expression. Upon challenge pADA co-immunization resulted in similarly decreased viral loads and age-associated morbidity and mortality in SARS-CoV-2 challenge models. These data support the use of aged mice as a model for age-associated decreased vaccine immunogenicity and infection-mediated morbidity and mortality in the context of SARS-CoV-2 and provide further support for the use of adenosine deaminase as a molecular adjuvant.